2018
DOI: 10.1111/liv.13938
|View full text |Cite
|
Sign up to set email alerts
|

The risk of hepatocellular carcinoma within and beyond the first 5 years of entecavir in Korean patients with chronic hepatitis B

Abstract: The incidence rate of HCC may not change significantly before and after 5 years of ETV therapy in Korean CHB patients. The risk of HCC in Asian CHB patients may remain in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
(47 reference statements)
2
18
0
1
Order By: Relevance
“…and Zhang et al 36 . In contrast, two recent long‐term studies 37,38 reported that there was no difference in the risk of cancer. One possible reason is that the incidence of HCC associated with the two drugs might be influenced by treatment time.…”
Section: Discussionmentioning
confidence: 97%
“…and Zhang et al 36 . In contrast, two recent long‐term studies 37,38 reported that there was no difference in the risk of cancer. One possible reason is that the incidence of HCC associated with the two drugs might be influenced by treatment time.…”
Section: Discussionmentioning
confidence: 97%
“…Although direct comparison is difficult, this rate was lower than the annual incidence rate of HCC in cirrhotic patients (3-7%), [45][46][47] but was higher than the yearly incidence rate of HCC (0.7-1.7%) in chronic hepatitis B patients who received antiviral therapy (AVT) for 5 years. 48,49 For those with any risk factors, the HCC recurrence risk for the next 5 years (5-10 years) was substantial (24.5-71.4%). We also noticed that the HCC recurrence risk was substantial among 100 patients without HBV, HCV, or cirrhosis, even after 5 recurrence-free years.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kim et al reported that the annual HCC incidence did not decrease significantly within and after the first 5 years of ETV treatment in a single‐center cohort of Korean patients either with or without cirrhosis. However, the annual incidence of HCC was significantly lower after 7 years of treatment than within the first 7 years in patients with cirrhosis 13 . Kim et al conducted a multicenter retrospective cohort study from Korea to develop an HCC risk score (mPAGE‐B), indicating that the annual incidence of HCC decreased significantly after 4 years of ETV/TDF treatment compared with within the first 4 years treatment, both in low‐risk (mPAGE‐B score ≤ 8), intermediate‐risk (mPAGE‐B score 9–12), and high‐risk (mPAGE‐B score ≥ 13) patients 37 .…”
Section: Resultsmentioning
confidence: 85%
“…We identified four studies that addressed changes in the incidence rate of HCC over time during treatment, 13,36–38 and baseline characteristics were summarized in Table S4. Papatheodoridis et al reported in a multicenter European study that the annual HCC incidence was significantly lower after 5 years of treatment than within the first 5 years of ETV/TDF treatment in Caucasian patients with cirrhosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation